A new species of Eryx (Serpentes: Erycidae) from Iran - Eskandarzadeh, Naeimeh; Rastegar-Pouyani, Nasrullah; Rastegar-Pouyani, Eskandar; Rastegar-Pouyani, Eskandar; Zargan, Jamil; Hajinourmohamadi, Ashkan; Nazarov, Roman A.; Sami, Soheil; Rajabizadeh, Mahdi; Nabizadeh, Hossein; Navaian, Majid (Zootaxa, 2020)
We describe a new species of the genus Eryx Daudin, 1803 from southern Iran that is morphologically closely related to the Indian sand boa, E. johnii. The new species, Eryx sistanensis sp. nov. has a distribution range from Zabol in the Sistan Region to the southern parts of Sistan & Baluchistan, as well as Hormozgan Province of Iran. Morphologically, E. sistanensis sp. nov. differs from E. johnii by having fewer dorsal scale rows at midbody and the tail tip is not as blunt as E. johnii. The genetic distance (p-distance) between the new species and the Indian sand boa is considerable (9.1% for cytb and 11.8% for COI).